(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. Application of porous carbon materials in various adsorption-catalytic and electrochemical processes requires optimization of their structural-sorption parameters and chemical properties of the surface layer. Modification of the surface of carbon materials with heteroatoms allows to significantly change its acid-base and hydrophilic-hydrophobic properties, which significantly expands the limits of application. A promising method of increasing the reactivity of the surface of carbon materials is the preparation of precursor materials that contain highly specific centers capable of further modification and preservation of the developed porous structure. This work is devoted to the study of the functionalization of the carbon surface with 2-phenylpropene (РhP) and to the study of its physicochemical properties and reactivity. Methods. Activated carbon was modified with 2-phenylpropene followed by its (oligo)polymerization and sulfonated with oleum. The surface morphology of the samples was studied by scanning electron microscopy (SEM), the specific surface area and the total pore volume were determined by the method of low-temperature nitrogen adsorption-desorption. The concentration of surface acid centers was determined by the titrimetric method. The thermal stability of the surface layer and the content of applied РhP in the modified samples were investigated by thermogravimetric analysis (TGA). The mechanisms of decomposition of the surface layer of the modified samples were studied by the method of thermoprogrammed desorption mass spectrometry (TPD-MS). The catalytic activity of the samples was studied in the model reaction of gas-phase dehydration of propan-2-ol. Results. Modification of activated carbon with 2-phenylpropene, followed by its (oligo)polymerization, is an effective method of increasing the concentration of active surface centers. This method allows introducing up to 0.77 mmol/g of thermally stable forms of РhP, capable of further sulfonation, into the surface layer of activated carbon. Studies of nitrogen adsorption-desorption demonstrate moderate changes in the specific surface area and porosity of activated carbon with the preservation of significant adsorption capacity. The methods of thermogravimetric analysis and thermoprogrammed desorption proved the high thermal stability of applied forms of 2-phenylpropene in the temperature range of 30–230 °С. Sulfated samples contain up to 0.72 mmol/g of strongly acidic SO3H groups and can be used as heterogeneous acid-base catalysts. Conclusions. Modification of activated carbon with 2-phenylpropene followed by its (oligo)polymerization is an effective method of increasing the concentration of active surface centers and obtaining heterogeneous acid-base catalysts containing up to 0.72 mmol/g of strongly acidic SO3H groups.